Needs and presence of temporary migrant workers in the regions of Quebec (Canada): From public data to a unified database. - Frozzini, Jorge; Arnaud, Vincent (Work, 2025)
Background: During the recent years of labour shortage, many employers and employer associations have been calling for the recruitment of more temporary migrant workers (TMW) in the province of Quebec. The various programs, the needs expressed by employers, and the problems encountered by TMWs remain largely unknown to the structures that receive these workers (municipalities, Regional County Municipalities or RCM ...) or help them (associations ...). The real number of TMWs in each local territorial division (Administrative regions, RCM and municipalities) remains unknown. It is therefore difficult to develop welcoming policies or an inclusive framework that meets the needs of these populations. Objective: To develop a more detailed knowledge of the presence of TMWs in Quebec and the needs expressed by employers. Methods: Design of a unified database to elaborate a statistical portrait of the needs expressed by employers and the presence of TMWs in the province of Quebec by stream of the Temporary Foreign Worker Program (TFWP), by skill level, and by territory from 2017 to 2022. An exploratory data analysis to summarize the main characteristics of this longitudinal sample using statistical graphics and maps was conducted. Results: There are substantial differences between regions and their territories regarding the streams of the TFWP, occupations and skills needed. The data also illustrate the prominence of some companies who hire a large number of TMWs in the province of Quebec and the effect of the COVID-19 lockdowns. Conclusion: Our analysis shows an increase of various types of TMWs in specific administrative regions and a gap in statistical data about workers from the TFWP for the organizing efforts of local environments (RCM, municipalities and their community sector) to respond to the needs of a growing number of these workers.